Sperm DNA damage and cytokines in varicocele: A case‐control study. (10th March 2021) - Finelli, Renata; Pallotti, Francesco; Cargnelutti, Francesco; Faja, Fabiana; Carlini, Tania; Rizzo, Flavio; Lenzi, Andrea; Paoli, Donatella; Lombardo, Francesco
Abstract: Varicocele is a vascular disease characterised by the abnormal enlargement of the pampiniform plexus veins and a well‐known cause of male infertility. The aim of this study was to investigate the relationship between sperm DNA fragmentation (SDF) and inflammation in the pathogenesis of varicocele. We included 84 varicocele patients and 85 normozoospermic healthy controls, further analysed according to the body mass index, the smoking habit (smokers/non‐smokers) and the varicocele severity (low/high grade). Semen parameters, SDF (by TUNEL) and inflammatory cytokines (by Luminex xMAP analysis) were evaluated. Varicocele patients showed significantly reduced semen parameters (volume, total sperm number, progressive motility, normal morphology) and increased SDF. Moreover, we observed a significant reduction of IFN‐γ, IL‐6, TNF‐α and an increase of IL‐10. No difference was reported according to the smoking habit, body mass index and varicocele severity. The observed cytokines pathway suggests the establishment of a chronic inflammatory condition, which may contribute to the alteration of semen quality. A thorough knowledge of the cytokine network might contribute to better understanding the link between inflammation and semen quality in varicocele and its impact on reproductive health.